HFCVD Diamond Film On Vanadium Carbide Interlayer Applied By Laser Cladding. Issue 1 (2017) - Damm, D. D.; Contin, A.; Trava-Airoldi, V. J.; Vasconcelos, G. de; Barquete, D. M.; Corat, E. J.
No abstract available